An exploration of the causes and effects of flight attendant fatigue in Turkish aviation - GÜNDÜZ, SEMA (My University, 2022)
The rapid growth in civil aviation operations in recent years has raised expectations from flight attendants. Their duties have been intensified, and flight attendants have become subject to physical and mental fatigue due to irregular sleep, inadequate rest time, and long working hours. This study investigates the causes and effects of fatigue among flight attendants of a Turkish airline company through a self-administrated questionnaire. The survey is run online to 152 flight attendants. The results show that the flight attendants have trouble falling asleep before flight duty. Before night flights and during layovers, the sleep duration is dramatically low. The results also reveal that factors related to scheduling, i.e., long duty days, night flights, consecutive working days, play an essential role in fatigue. Thus, airline companies should revise their scheduling practices. On balancing work and social life, men struggle more than women, and married flight attendants have more difficulty than single ones. The findings provide valuable insights for airline companies and policymakers to seriously manage fatigue-related factors to ensure the safety of aviation operations and the well-being of flight attendants.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Airline companies; Cabin crew; Fatigue; Flight attendant; Turkey